2009
DOI: 10.3168/jds.2008-1626
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determination of the onset of heat stress on daily milk production in the US Holstein cattle

Abstract: Existence of individual variation in the onset of heat stress for daily milk yield of dairy cows was assessed. Data included 353,376 test-day records of 38,383 first-parity Holsteins from a random sample of US herds. Three hierarchical models were investigated. Model 1 inferred the value of a temperature-humidity index (THI) at which mean yield began to decline as well as the extent of that decline. Model 2 assumed individual variation in yield decline beyond a common THI threshold. Model 3 additionally assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 15 publications
4
61
0
1
Order By: Relevance
“…Bernabucci et al (2014), based on the negative genetic correlation of milk, protein, and fat production with heat stress in 3 lactations, claimed that selection for higher production itself leads to a decline in genetic merit for heat tolerance. Similar to the results obtained here, Sánchez et al (2009) also reported negative correlations between the intercept and slope for both additive genetic and permanent environmental effects of milk yield. As an alternative to overcome the antagonism between production and tolerance to heat stress, Carabaño et al (2014) suggested eigendecomposition of the random regression coefficient matrix to produce new variables that would prevent the antagonistic relationship between the intercept and slope of the reaction norms of animals.…”
Section: Discussionsupporting
confidence: 89%
“…Bernabucci et al (2014), based on the negative genetic correlation of milk, protein, and fat production with heat stress in 3 lactations, claimed that selection for higher production itself leads to a decline in genetic merit for heat tolerance. Similar to the results obtained here, Sánchez et al (2009) also reported negative correlations between the intercept and slope for both additive genetic and permanent environmental effects of milk yield. As an alternative to overcome the antagonism between production and tolerance to heat stress, Carabaño et al (2014) suggested eigendecomposition of the random regression coefficient matrix to produce new variables that would prevent the antagonistic relationship between the intercept and slope of the reaction norms of animals.…”
Section: Discussionsupporting
confidence: 89%
“…In both studies, heritabilities for performance traits (milk production or carcass weight at slaughter) were found to increase as a function of THI. In another approach, a hierarchical Bayes model has been proposed, where both threshold of heat stress at which performance start to decrease and rate of decline from heat stress could be estimated (Sá nchez et al, 2009). On the basis on Holstein milk production data, they found that both parameters are heritable traits (0.32 to 0.56, respectively), suggesting that selective improvement of such characters is possible.…”
Section: Strategies To Alleviate Heat Stress In Farm Animalsmentioning
confidence: 99%
“…The pattern of individual deviations is expected to be determined by differences in the HS threshold and the magnitude of the negative effect of HS among cows. Estimation of individual thresholds under BL models has been proven to be cumbersome (Sánchez et al, 2009) because of the complexity of the needed models. Again, polynomial functions have been used to describe individual deviations to avoid these drawbacks (Brügemann et al, 2011;Hammami et al, 2013;Carabaño et al, 2014).…”
Section: Introductionmentioning
confidence: 99%